We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
64
1
avatar

http://prntscr.com/miz1n5

 Feb 10, 2019
 #1
avatar
0

Look carefully at the statement given:
3 + (5 + 4) = (5 + 4) + 3
Look at Left-hand side:
a = 3 and b =(5 + 4)
Now, look at Right-hand side:
b = (5 + 4)  and  a = 3. Therefore:
a + b = b + a       sub the values of a  and b above into this equation:
3 + (5 + 4) = (5 + 4) + 3
And that is why G is the answer. Got it?.

 Feb 10, 2019

26 Online Users

avatar
avatar
avatar